Changes in Inflammatory Cytokine Levels in Rectal Mucosa Associated With Neisseria gonorrheae and/or Chlamydia trachomatis Infection and Treatment Among Men Who Have Sex With Men in Lima, Peru - Clark, Jesse L. (2024)
Background. Neisseria gonorrheae and Chlamydia trachomatis are associated with mucosal inflammation and human immunodeficiency virus 1 (HIV-1) transmission. We assessed levels of inflammatory cytokines in men who have sex with men (MSM) with and without rectal gonorrhea and/or chlamydia in Lima, Peru. Methods. We screened 605 MSM reporting condomless receptive anal intercourse for rectal N. gonorrheae/C. trachomatis using nucleic acid testing. We identified 101 cases of gonorrhea and/or chlamydia and randomly selected 50 N. gonorrheae/C. trachomatis positive cases and matched 52 negative controls. We measured levels of IL-1β, IL-6, IL-8, and TNF-α in rectal secretions. Tests for HIV-1, rectal N. gonorrheae/C. trachomatis, and mucosal cytokines were repeated after 3 and 6 months. Cytokine levels in cases and uninfected controls were compared using Wilcoxon rank-sum tests and linear regression. Results. MSM with gonorrhea/chlamydia had elevated levels of all cytokines in rectal mucosa compared with matched controls (all P values <.001). Following antibiotic treatment there were no significant differences in cytokine levels at 3- or 6-month followup evaluations (all P values >.05). Discussion. Rectal gonorrhea/chlamydia infection is associated with transient mucosal inflammation and cytokine recruitment. Our data provide proof of concept for rectal sexually transmitted infection screening as an HIV prevention strategy for MSM.